Impulsivity, risk‐taking, and distractibility in rats exhibiting robust conditioned orienting behaviors. Issue 2 (17th August 2014) - Olshavsky, Megan E.; Shumake, Jason; Rosenthal, Alek A.; Kaddour‐Djebbar, Amine; Gonzalez‐Lima, F.; Setlow, Barry; Lee, Hongjoo J.
<x xml:space="preserve">Abstract</x> When a neutral cue is followed by a significant event such as food delivery, some animals become engaged with the cue itself and acquire cue‐directed behaviors. One type of cue‐directed behavior is observed following insertion of a lever used as a conditioned stimulus (CS). Rats showing robust approach behavior to the lever also display impulsivity and altered attention, as compared to rats showing behavior directed toward the reward delivery location. The current study used a light CS to categorize rats' propensity for cue‐directed behavior, and assessed whether individual differences in impulsivity and related behaviors still emerged. During the light–food pairings, some rats displayed enhanced rearing or orienting to the light (Orienters) prior to showing food cup approach behavior, while other rats only showed food cup approach behavior (Nonorienters). Our results showed that Orienters made more impulsive and risky decisions in two different choice tasks, and were quicker to leave a familiar dark environment to enter a novel bright field. Orienters also showed less accurate target detection when a visual distractor was introduced during an attentional challenge. Our current study suggests that light CS‐induced rearing/orienting behavior might not necessarily share an identical mechanism with lever CS‐approach behavior in predicting impulsivity‐related behaviors.